THE ROLE OF YOUTH IN PRESENTING DEMOCRACY - Muddapu, Hasini (Young Scholars Grinchenko – Seton International Journal, 2026)
Democracy is often considered a destination or a finished product characterized by rules, institutions, or constitutional guarantees. As long as we recognize democracy and its ideals, the world will be fine. Yet, history teaches us a different story. Democracy is a living system. Similar to any other evolving organism, it constantly requires adaptation, nourishment, and defense when it is taken for granted. The current global climate of the world shows how this system is under immense stress. The challenges range from aggressive authoritarianism to eroding public trust in international institutions. At the center of this tension lies the most assertive and influential force in global politics: the youth. For years, youth have been seen as simply a demographic that needs to be mobilized during elections. However, around the world, young people are progressively proving to be activists of political change. Rather than simply inheriting the previous systems of society, they are actively involved in reshaping global governance. Of course, this is not a simple journey. For many young people, democracy is not a political concept; it is integrated into their daily lives and drives them to advocate for leadership, justice, and reconstruction. The Atlantic Council reports how many young Ukrainians have worked to integrate technology into their daily lives during wartime so that they can document war crimes and fight for international accountability. Moreover, many young, inspiring individuals in Ukraine are working towards building an authentic human connection by being involved in youth movements. These specific movements encourage discussions about geopolitics, mental health, and other topics. Through these opportunities, students are able to make a difference and be heard. For Ukraine specifically, it allows them to connect with youth programs in Europe and talk about their stories. Inspiring and hopeful young individuals view themselves as the primary force for recovery in Ukraine. Every day, they are committed to advocating for a better Ukrainian democracy. They fight for things like transparency and take measures against corruption. In the era of international media, storytelling and human connection are far more effective than the formal approaches of the past. They acknowledge that the country’s future depends on accountability, reliable government, and sustainable partnerships.